Natural compounds boldine and menthol are antagonists of human 5‐HT3 receptors: implications for treating gastrointestinal disorders. Issue 6 (8th April 2014) - Walstab, J.; Wohlfarth, C.; Hovius, R.; Schmitteckert, S.; Röth, R.; Lasitschka, F.; Wink, M.; Bönisch, H.; Niesler, B.
Abstract Background Impaired 5‐HT3 receptor function is likely involved in the pathogenesis of functional gastrointestinal disorders (FGID) and 5‐HT3 receptor antagonists are effective treatments for chemotherapy‐induced nausea and vomiting (CINV) and irritable bowel syndrome (IBS). The monoterpene alcohol menthol and the aporphine alkaloid boldine combat symptoms of gastrointestinal diseases; both interact with other members of the Cys‐loop ligand‐gated ion channel family and may therefore also act on 5‐HT3 receptors. Methods The impact of boldine and menthol on human recombinant homomeric 5‐HT3A‐ and heteromeric 5‐HT3AB receptors in HEK293 cells was determined by radioligand binding, a luminescence‐based Ca2+ assay, and a membrane potential assay. 5‐HT3 protein and mRNA expression was assessed in human colon tissue. Key Results Boldine and menthol inhibited the 5‐HT‐induced activation of 5‐HT3 receptors in the low and middle micromolar range, respectively. Boldine was a competitive antagonist of both receptors being 6.5‐ to 10‐fold more potent at 5‐HT3A‐ vs 5‐HT3AB receptors. Menthol non‐competitively and stereoselectively inhibited both receptors: In contrast to (+)‐menthol, (−)‐menthol was significantly more potent toward 5‐HT3A‐ vs 5‐HT3AB receptors. We show co‐expression of 5‐HT3A and 5‐HT3B subunits in the human gut epithelium, the lamina propria, the myenteric plexus, and the muscular cell layer. Conclusions & Inferences The demonstrated 5‐HT3 inhibitory effects may be relevant for boldine's and menthol's alleviating properties on FGID and may encourage clinical studies with the compounds or the plant extracts for CINV and IBS treatment. The found receptor‐discriminative properties make boldine and (−)‐menthol to potentially useful tools for analyzing structural differences between these receptor subtypes.